The Ijtihad Method: Ijma' and Qiyas as Sources of Islamic Law from the Perspective of Usul Fiqh - Saputri, Sherli Dwi Andri; Ardi , Hafidz; Khadijah, Khadijah; Sari, Widya (The Future of Education Journal, 2025)
This article examines the position and methodological foundation of Ijma’ (consensus of scholars) and Qiyas (analogical reasoning) as essential sources in Islamic legal theory. As new socio-economic and technological issues emerge, classical jurisprudential approaches require reinterpretation to maintain relevance. This study employs a qualitative descriptive method through literature review of classical and contemporary works in Ushul Fiqh. The findings show that Ijma’ provides definitive legitimacy to legal rulings when scholars reach unanimous consensus, while Qiyas enables legal extension based on shared effective causes (‘illah). However, debates remain regarding the authority of silent consensus (Ijma’ Sukuti) and the limit of analogical reasoning in complex modern cases. The novelty of this research lies in systematically linking classical arguments with contemporary legal challenges, offering a conceptual model for applying Ijma’ and Qiyas in modern jurisprudential contexts, especially in digital and socio-ethical issues.